Beauty Goes Green: Effects of Eco-Label and Price Sensitivity on Filipino Gen X and Z’s Sustainable Purchasing Behaviour - Nina Isabel Bautista; Jillian Shamira Palmiano; Alyanna Raiza Reyes; Ysabel Maria Louise San Juan; Antonio Etrata Jr. (East Asian Journal of Multidisciplinary Research, 2023)
Several companies have adopted sustainability as a business approach to protect the social, ecological, and economic environments. This study aims to determine the influence of eco label and price sensitivity on green purchasing behavior of Filipino Gen X and Z consumers and to identify their perception towards them. An online questionnaire was distributed to 385 respondents, and the data gathered for this quantitative study were analyzed through descriptive statistics, t-test, and multiple linear regression. Results show that only price sensitivity significantly affects the purchasing behavior of Gen X. While both eco-label and price sensitivity significantly affects Gen Z’s purchasing behavior. Moreover, the presence of an eco-label influences their buying behavior since they are more knowledgeable of its relevance in products.